Nickel exploration with 3D seismic - Lake Lefroy, Kambalda, WA - Urosevic, Milovan; Kepic, Anton; Sheppard, S.; Johnson, D. (Society of Exploration Geophysics, 2008)
The first experimental 2D high resolution seismic reflection was recorded in 2005 over McLeay nickel deposits, Lake Lefroy, Kambalda, Western Australia. Seismic results indicated that these deposits may have a seismic signature. The complexity of the seismic pattern also suggested that 3D seismic may be necessary for exploration of McLeay deposits. Subsequent pilot high resolution 3D seismic survey conducted in 2007 confirmed the potential of reflection seismic for exploration at this site. Finally in 2008, a 10 Km2 high-resolution 3D seismic survey was acquired. Extreme conditions at the lake proved challenging for the application of seismic methods and required modification of the conventional seismic acquisition practice. In this paper we document and discuss acquisition and processing issues related to the specifics of the salt lake as well as the seismic signature of nickel deposits.